IRIDE: Innovazione e Sostenibilità: le Sfide e le Opportunità dell’Industria di Osservazione della Terra - Sylos Labini, Giovanni; Zotti, Massimo; Royer, Eduard (GEOmedia, 2024)
IRIDE, a cutting-edge constellation in the Earth Observations scenario, stands out for its ability to integrate optical, SAR and hyperspectral sensors under a single command system, creating new opportunities for the operational use of satellite data. The project was born and developed thanks to the PNRR program, which directed its development and defined the implementation methods, following an AGILE method inspired by the software development practices of the same name. Below we develop the challenges and opportunities of this program through a lens particularly focused on the Italian industrial landscape. This analysis aims to explore IRIDE as a catalyst of innovation and growth for the national industry in the sector. From this point of view, the importance of the project emerges not only as a significant technological undertaking, but as a milestone that marks a turning point for the Italian industrial ecosystem in Earth observation.